L-Lysine/l-arginine/l-cysteine synergistically improves the color of cured sausage with NaNO2 by hindering myoglobin oxidation and promoting nitrosylmyoglobin formation. (30th June 2019) - Ning, Cheng; Li, Linxian; Fang, Hongmei; Ma, Fei; Tang, Yuxiang; Zhou, Cunliu
Highlights: Lysine/arginine/cysteine can effectively reduce Mb(Fe 2+ ) oxidation. Lysine/arginine/cysteine synergistically improves the color of sausages with NaNO2 . Lysine/arginine/cysteine synergistically decreases residual nitrite. Lysine/arginine/cysteine synergistically increases nitrosylmyoglobin. The results are of interest in the meat industry. Abstract: This study aimed to evaluate the effects of l -lysine (Lys)/l -arginine (Arg)/l -cysteine (Cys) on the color of cured sausage and the possible mechanism underlying these effects. The results indicated that the combined addition of Arg/Lys/Cys and NaNO2 effectively increased the a* values and nitroso pigment content but decreased the MetMb(Fe 3+ ) content in cured sausage, compared with the individual addition of Arg/Lys/Cys and NaNO2 . The cured sausage treated with combined Arg/Lys/Cys and NaNO2 contained significantly lower residual nitrite than those treated with only NaNO2 . UV-vis spectroscopy and electron paramagnetic resonance spectroscopy revealed that pentacoordinate nitrosyl ferrohemochrome was the main pigment component in the cured sausage treated with NaNO2 or combined Arg/Lys/Cys and NaNO2 and higher content in the latter one. The results suggest that Arg/Lys/Cys hindered myoglobin oxidation and promoted pentacoordinate nitrosylmyoglobin formation, which could contribute to the improved color of cured sausage. The results are of interest in the meat industry.